A study into the effect of concentration process on the yield of rotenone from the extract of local plant species (Derris elliptica) - Zubairi, Saiful Irwan; Sarmidi, M. R.; Aziz, R. A. (2004)
Bio-pesticides are becoming increasingly important as pest management tools in various cropping systems in the tropics essentially to remedy problems associated with the indiscriminate use of ‘hard’ inorganic pesticide and interest in organic agriculture. In the few decades, many bio-pesticidal products, both microbial-based (bacteria, fungi, microsprodia, entomopathogenic nematodes, viruses) and plant-based botanicals (rotenone and azadiracthin) had been studied for use against insect pests in the tropics. In this paper, the effect of the concentration process towards the yield of rotenone; mg and its concentration; mg/ml are studied extensively. The raw plants were collected from Kota Johor Lama, Johor and sorted to collect the root and stem. Only the root and stem were utilized as a raw material of the extraction process. The root and stem were extracted using the Normal Soaking Extraction (NSE) at 28 0C to 30 0C with 95 % (v/v) of acetone as a solvent and the solvent-to-solid ratio of 10 ml/g). The extraction was carried out for 24 hours. The liquid crude extract was concentrated further (the solvent removed under reduced pressure) using the rotary evaporator at 50 0C and 80 mbar of vacuum pressures. The fractions of the liquid crude extract were collected for each interval time (15 mins/1.0 ml/fraction). Each fractions were diluted 1/100 with acetone and further cleaned up prior to determination of rotenone content; mg and concentration; mg/ml by using the High Performance Liquid Chromatography (HPLC). Significant effect of the concentration process against the yield of rotenone; mg was recorded and shows a significant thermal degradation or dissipation of rotenone content at higher operating temperature. The possibilities for better exploitation and identification of the effective operating parameters will be discussed.